Effect of lidocaine cream analgesia for chest drain tube removal after video-assisted thoracoscopic surgery for lung cancer: a randomized clinical trial. Issue 1 (20th November 2019) - Watanabe, Shin-nosuke; Imai, Kazuhiro; Kimura, Tetsu; Saito, Yoshitaro; Takashima, Shinogu; Matsuzaki, Ikuo; Kurihara, Nobuyasu; Atari, Maiko; Matsuo, Tsubasa; Iwai, Hidenobu; Sato, Yusuke; Motoyama, Satoru; et al.
Abstract : Background and objectives: Pain management makes an important contribution to good respiratory care and early recovery after thoracic surgery. Although the development of video-assisted thoracoscopic surgery (VATS) has led to improved patient outcomes, chest tube removal could be distressful experience for many patients. The aim of this trial was to test whether the addition of lidocaine cream would have a signiﬁcant impact on the pain treatment during chest tube removal from patients who had undergone VATS for lung cancer. Methods: This clinical trial was a double-blind randomized study. Forty patients with histologically confirmed lung cancer amenable to lobectomy/segmentectomy were enrolled. All patients had standard perioperative care. Patients were randomly assigned to receive either epidural anesthesia plus placebo cream (placebo, Group P) or epidural anesthesia plus 7% lidocaine cream cutaneously around the chest tube insertion site and on the skin over the tube's course 20 min (Group L) before chest drain removal. Results: Visual analog scale (VAS) scores were higher in Group P (median 5, IQR, 3.25-8) than in Group L (median 2, IQR, 1-3). Pain intensities measured using a PainVision system were also higher in Group P (median 296.7, IQR, 216.9–563.5) than Group L (median 41.2, IQR, 11.8–97.0). VAS scores and the pain intensity associated with chest drain removal were significantly lower in Group L than Group P (p=0.0002 vs p<0.0001). Conclusion: Analgesia using lidocaine cream is a very simple way to reduce the pain of chest tube removal after VATS. Trial registration number: UMIN000013824.